Research on the Theoretical Framework and Practical Countermeasures of Junior Middle School Mathematics Interdisciplinary Study based on STEM - Yang Wanwei; Chen Lijuan (SHS Web of Conferences, 2024)
At present, the interdisciplinary learning ability and level of junior middle school have become an important symbol to measure the teaching level of junior middle school. As the basic theory and important tool of science learning, it is of great significance to vigorously promote the interdisciplinary learning of junior middle school mathematics with mathematics as the core subject. This paper first analyzes the research background and current situation of interdisciplinary learning of junior middle school Mathematics from the perspective of STEM (i.e. Science, Technology, Engineering, Mathematics). Then, the paper constructs the theoretical framework of junior middle school mathematics interdisciplinary learning based on the research of science subject, technology subject and engineering subject. Finally, from the three dimensions of experimental teaching, information technology and scientific spirit, this paper puts forward the practical strategy of junior middle school mathematics interdisciplinary learning.